Moving away from aid: The experience of the Republic of Korea - Rachael Calleja; Annalisa Prizzon (Overseas Development Institute (ODI), 2019)
The Republic of Korea is one of few countries to have gone from recipient of official development assistance (ODA) to joining the OECD Development Assistance Committee (DAC). The Republic of Korea's transition and graduation from ODA was completed more than 20 years ago, therefore providing an opportunity to map the entire path towards graduation. This case study analyses how the Republic of Korea managed its transition from aid, looking at the type of cooperation the country received and expected from its development partners from the end of the second world war. The report details lessons from the Republic of Korea's poverty eradcation and sustainable growth strategy, as well as reviews the approaches to strengthen its position in global dialogue and international affairs. The Republic of Korea study forms part of a larger project that sets out to investigate country experiences of and key lessons from the transition and graduation from ODA. The other country studies are Chile, Botswana and Mexico.
Keywords: 330